2022
DOI: 10.3389/fnut.2022.846333
|View full text |Cite
|
Sign up to set email alerts
|

Residue, Dissipation Pattern, and Dietary Risk Assessment of Imidacloprid in Chinese Chives

Abstract: The demand for Chinese chives is growing as they are also rich in vitamins, fiber, and sulfur nutrients. Chinese chives should be sprayed with imidacloprid to control pests and diseases to safeguard their yield and to meet the demands of East Asian consumers for Chinese chives. Overspraying of imidacloprid can lead to residues in Chinese chives, posing a severe risk to human health. To reduce the harmful effects of imidacloprid residues on humans, we investigated the imidacloprid dissipation pattern and the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…According to Zhai et al (2022) and Durán-Quirós et al (2017), pesticide residues gradually decrease over time, and the rate of decrease varies by various environmental factors, and plant and pesticide characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Zhai et al (2022) and Durán-Quirós et al (2017), pesticide residues gradually decrease over time, and the rate of decrease varies by various environmental factors, and plant and pesticide characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The figure 4 shows the logarithmic dissipation of imidacloprid for the two types of application, evidencing that AAF and GPP also caused a staggered dissipation in the peel and pulp of the avocado as time increases. In a study of imidacloprid dissipation by Zhai et al (2022) in Chinese onion (Allium tuberosum) they observed dissipation dynamics consistent with first order kinetics, with final residual levels between 0.00923 and 0.166 mg.kg -1 below the MRL (1 mg.kg -1 ) with a risk assessment index <1 indicating that they are safe for consumption.…”
Section: 𝑌𝑌 = 𝐵𝐵0𝑒𝑒 𝐵𝐵1𝑋𝑋𝑋𝑋mentioning
confidence: 94%
See 1 more Smart Citation